The Effect Of Audit Tenure, Auditor Switching, Leverage And Hood Reputation On Audit Lag - Nurlarasati, Haliza; Parinduri, Aina Zahra (Innovative: Journal Of Social Science Research, 2024)
Examining variables including auditor tenure, auditor switching, leverage, and KAP reputation allowed the researchers to answer the question, "What factors influence audit lag?" This study's population consists of companies listed on the Indonesia Stock Exchange (IDX) in the food and beverage subsector from 2018 to 2022 that do not engage in cyclical consumer spending. Quantitative data is utilized in this study. A purposive sample strategy was used to randomly select 35 companies for the sampling method. The research methodology used in this study is multiple linear regression. The results show that audit tenure and auditor switching have no effect on audit latency, whereas leverge and KAP reputation have a positive and negative relationship, respectively. The findings suggest that in order to cut down on audit delays, companies should put an emphasis on leverage and KAP reputation